A Study the Lean Manufacturing and Supply Chain Management to Optimize Inventory (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A supply chain is an integrated system that transfers goods or services from a supplier to a final customer through the use of operations, technology, human resources, & information sharing. SCM has garnered more attention lately because of its focus on the material, information, & financial flow from suppliers to customers or vice versa. SCM's inventory control is a big problem. Inventory is the term for idle products that are stored in various forms & locations, waiting to be used or sold. The procedure of confirming that the right amount and quality of material is available when needed while minimizing working capital & storage and ordering expenses is known as inventory control. The optimization of inventory in the SCM for lean manufacturing is the main goal of this study.